Penyuluhan Pemuda Cerdas Berpartai Politik Di Desa Jayakarta Kabupaten Bengkulu Tengah - Solichin, Solichin; Apriyanto, Muhammad Andreas; Kurniawan, Wawan; Kaswandi, Hendra; Afrilia, Riski Maharani (Jurnal Kewirausahaan dan Bisnis, 2022)
This activity aims to determine the role of political education agents on the implementation of political education of the younger generation. In addition, this activity also aims to determine the impact of political education of the younger generation on the implementation of political participation. The results of the activity show that the role of agents on the implementation of political participation of the younger generation has not been running well.Furthermore, political education of the younger generation has not had a significant impact on the implementation of political participation. Through this activity we suggest the need to intensify the implementation of political socialization periodically to villages. The need for the government and stakeholders to optimize the role of each political education agent as a partner for the implementation of political education. The need for the younger generation to be given wider opportunities and responsibilities in the public sphere such as being involved as members of political parties, or other socio-political organizations.